Phytoextraction of lead through Helianthus annuus and its effects on the growth of Cajanus cajan - Adarsh pandey2, Vijay Kumar Sinhal1, Vipin Yadav1 and (Current Botany, 2011)
To evaluate the effects of Pb (Lead Nitrate) on the growth of Cajanus cajan and it`s remediation, the two varieties of Cajanus cajan (Var. UPAS-120 & Var. ICPL-151) were sown in two different set of fields. Both the set of field were irrigated with different doses of Pb (19, 20, & 21 mg lit-1). In the second set of experiment the same varieties of Cajanus cajan were intercropped with Helianthus annuus to remediate the Pb from soil.Ã‚Â A concentration dependent decrease was noticed in all the growth parameters (i.e. plant height, fresh & dry Weight of plants, chlorophyll content, and protein content) and biochemical parameters (enzymes like Nitrate reductase, Glutamine oxo glutarate amino transferase and Glutamate dehydrogenase, activities) studied but the proline content was increased with increase in concentration of Pb. The maximum reduction (% of control) was noticed under the influence of higher dose of Pb (21 mg lit-1) in both the varieties of Cajanus cajan. Variety UPAS-120 was found to be more susceptible to Pb toxicity than variety ICPL Ã¢â‚¬â€œ 151. <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â In second set of experiment (where Cajanus cajan was intercropped with Helianthus annuus) a significant recovery of the toxic effects of Pb was noticed in all the parameters studied.Ã‚Â Atomic absorption spectrophotometer study suggested that the accumulation of Pb through Helianthus annuus grown in Pb treated soil was higher than non-treated soil. The results of the present investigation reveals that Helianthus annuus can be used as phytoremediator to reclaim the soil contaminated with Pb.